The urban regulation of rural land from the perspective of the new Law for the Promotion of Territorial Sustainability in Andalusia (Andalusian Land Law) - Galacho-Jiménez, Federico Benjamín; Reyes-Corredera, Sergio Jesús (Asociación Española de Geografía, 2022)
Since their inception, various urban planning laws have focused on meeting the growth needs of cities, with urban planning as a discipline paying minimal attention to rural settlement planning. It can, therefore sound clichéd to say that urban planning legislation has been mainly concerned with regulating urban and developable land, with residual or negative status being given to undevelopable or rural land. This has had major territorial impacts that continue to this day. The proposed subject of this paper is considered timely and topical, and its main objective is to analyse whether the planning instruments proposed in the Law for the Promotion of Territorial Sustainability in Andalusia (LISTA, acronym in Spanish) for rural settlements and scattered buildings can help regulate rural land dynamics in Andalusia. To do so, we will first model the patterns of settlement formation and isolated dwellings on rural land using geostatistical methods, and then carry out an analysis of the provisions of these latest rural land management laws, which will affect the planning regulations of this land in the coming years.
Keywords: Urbanismo; Urban planning; Territorial planning; Spatial analysis; Urban sprawl; Rural area; Planeamiento urbanístico; Planificación territorial; Análisis espacial; Urbanismo difuso; Espacio rural